Environment Pollution Modeling on the Base of Quick Computing Models - Rusakova, T. I.; Berlov, O. V.; Gubin, O. I.; Gunko, O. Yu.; Mashykhina, P. B. (Science and Transport Progress, 2025)
Purpose. Development of a fast calculation models for determining zones of ground waters and air chemical pollution during the emission of chemically hazardous substances from anthropogenic sources of pollution. To model the process of passive impurity transfer in ground waters and in atmospheric air, the G. Marchuk model is used, which takes into account the speed and direction of the flow, the intensity of the emission of chemically hazardous substances, and atmospheric diffusion (dispersion in round waters). Methodology. The process of ground waters and air pollution modeling is based on the numerical integration of the mass transfer equation (G. Marchuk model). Two numerical models were built. One numerical model was built to simulate ground waters pollution. Another numerical model was built to simulate air pollution. The construction of a numerical models of the impurity propagation process was carried out by splitting of the mass transfer equation (G. Marchuk model). Then a variable-triangular finite-difference decomposition schemes were used for numerical integration. The unknown value of the concentration of a chemically hazardous substance is carried out using explicit formulas. A set of applied programs has been developed based on the constructed numerical models. Findings. A set of applied programs has been developed based on the constructed numerical models. The results of numerical calculations are presented, showing the efficiency of the proposed numerical models. Originality. Proposed numerical models of mass transfer allow to compute quickly the areas of chemical air pollution due to the emission of toxic substances from anthropogenic sources of pollution. Practical value. Based on the proposed numerical models, a computer code has been developed. The developed models and computer code make it possible to estimate the size and intensity of environmental pollution, and can be used in solving the problem of assessing the negative impact on the ground waters and air from different sources. The results of numerical calculations show the operability of the proposed models.